Effect of anti-apoptotic drug Z-VAD-FMK on in vitro viability of dog follicles - Costa Pereira, Leda Maria [UNESP]; Thongkittidilok, Chommanart; Lopes, Maria Denise [UNESP]; Songsasen, Nucharin (Elsevier, 2018)
It is recognized that ovarian follicular atresia is associated with apoptosis, and the most important effector of cell death is caspase-3. The aim of this study was to investigate the influence of anti-apoptotic drug Z-VAD-FMK on in vitro follicle growth in the domestic dog. Ovaries were obtained from peri-pubertal and adult domestic dogs, and cortical fragments recovered and incubated on 1.5% (w/v) agarose gel blocks within a 24-well culture plate containing Minimum Essential Medium Eagle-Alpha Modification (αMEM) supplemented with 4.2 μg/mL insulin, 3.8 μg/mL transferrin, 5 ng/mL selenium, 2 mM L-glutamine, 100 μg/mL of penicillin G sodium, 100 μg/mL of streptomycin sulfate, 0.05 mM ascorbic acid, 10 ng/mL of FSH and 0.1% (w/v) polyvinyl alcohol in humidified atmosphere of 5% CO2 and 5% O2. The cortices were randomly allocated in six treatments: 1) 10 ng/mL EGF (EGF V0); 2) 10 ng/mL of EGF plus 1 mM Z-VAD-FMK (EGF V1); 3) 10 ng/mL of EGF and 10 mM Z-VAD-FMK (EGF V10); 4) 1 mM Z-VAD-FMK; 5) 10 mM Z-VAD-FMK and (6) no EGF and Z-VAD-FMK supplementation (Control). The cortices were processed for histology and assessed for viability (based on morphology), density of structurally normal follicles, and diameter immediately after collection (non-culture Control) or after 3 or 7 days of in vitro incubation. Evaluation of mRNA expression of Cas3 in fresh cortices and those incubated for 3 days was performed using real-time PCR. Histological analysis revealed that in vitro incubation decreased (P < 0.05) follicle viability and density compared to the fresh, non-culture control. Addition of 10 μM of Z-VAD-FMK alone to the culture medium sustained follicle viability at Day 3, but did not impact follicle diameter when compared to the other treatment groups (p < 0.001); however, the beneficial benefit of this anti-apoptotic drug diminished after 7 days of incubation. Furthermore, Z-VAD-FMK supplementation did not impact Cas3 expression. The findings demonstrated that dog ovarian tissues are highly susceptible to in vitro incubation and Z-VAD-FMK supported short-term survival of dog follicles enclosed within the ovarian cortex.
Keywords: Anti-apoptotic drug; Caspase; Dogs; Follicles